Health Risk Assessment From Heavy Metals Derived From Drinking Water and Rice, and Correlation With CKDu - Kulathunga, Mudalige R. D. L.; Wijayawardena, M. A. Ayanka; Naidu, Ravi; Wimalawansa, Sunil J.; Rahman, Mohammad Mahmudur (Frontiers in Water, 2022)
Rice is the staple food of most Asians, including Sri Lankans. It is cultivated extensively in the dry zonal regions in Sri Lanka such as the Polonnaruwa district, where the prevalence of chronic kidney disease of unknown etiology (CKDu) is higher. We investigated the concentrations of potentially toxic heavy metal(loid)s in groundwater and locally produced rice and correlated their exposure with the prevalence of CKDu. We studied human health exposure risks such as total daily intake (TDI), hazard quotient, hazard index, and carcinogenic risk (CR) from the consumption of groundwater and rice. In well-water, the concentrations of heavy metal(loid)s, cadmium (Cd), arsenic (As), and lead (Pb) were below the World Health Organization (WHO) stipulated allowable limits. Except for Pb, contents of other heavy metal(loid) in all rice samples were lower than maximum permissible limits by the WHO (0.02 mg/kg). Twenty-three per cent (23%) of rice samples analyzed exceeded the permissible limit for TDI of Pb, and analysis of hazard index for Cd, As, and Pb revealed 26% of rice samples could result in a health risk through the consumption of rice in this population. Further, the outcome depicted no CR of Cd, As, and Pb by consuming rice in this study area. We recommended further studies and investigations to minimize or eliminate potential risks from chronic Pb exposure to consumers.